Pengaruh Media Matching Word Game Terhadap Keaktifan Belajar Bahasa Indonesia Di Kelas V SD Muhammadiyah Sangatta Utara - A. Dia Mandasari; Tri Velyna; Muhammad Imam Syafi’i (Civiliza Publishing, Indonesia., 2026)
This study was conducted in response to the low level of student engagement in Indonesian language learning. It aimed to examine the difference in student engagement before and after the implementation of the Matching Word Game learning media in the experimental group, the difference in student engagement before and after instruction without the Matching Word Game learning media in the control group, and the difference in student engagement between the experimental group, which received instruction using the Matching Word Game learning media, and the control group, which received conventional instruction without the media. This study employed a quantitative approach using an experimental method with a Non-Equivalent Control Group Design. The participants consisted of 25 fifth-grade students from Class VC as the experimental group and 24 fifth-grade students from Class VB as the control group. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive and inferential statistics. Since the data were not normally distributed, the hypotheses were tested using the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test with the assistance of SPSS version 27. The findings revealed a significant improvement in student engagement in Indonesian language learning among students in the experimental group after the implementation of the Matching Word Game learning media, whereas no significant difference was found in the control group. Furthermore, a significant difference in student engagement was observed between the experimental and control groups. These findings indicate that the Matching Word Game learning media is effective in enhancing student engagement in Indonesian language learning among fifth-grade elementary school students.